The Semantic and Sociolinguistic Dimensions of the Word "Qawwamun" in the Qur'anic Text: A Critical Study on the Authority of the Husband in Family: البعد الدلالي والسوسيولغوي لكلمة "قَوَّامُونَ" في النص القرآني: دراسة نقدية عن سلطة الزوج في الأسرة - Pallawagau, Baso; Jahantab, Zakirah; Alsadiq, Sherif Muhammad (Langkawi: Journal of The Association for Arabic and English, 2025)
This research focuses on the semantic and sociolinguistic dimensions of the word qawwamun in verse 34 of Surah An-Nisa, to examine various interpretations throughout history. The primary objective of this research is to analyze the semantic and sociolinguistic meaning of qawwamun in the Quranic text and to determine its meaning in linguistics and social contexts, to emphasize the concept of a husband's authority within the family. The research explores the linguistics analysis of this term based on its lexical meaning and to compare it with the sociolinguistics the context that influences its interpretation in Muslim societies. Additionally, it discusses various interpretations ranging from traditional understandings, which consider qawwamah as the absolute authority of men, to modern interpretations that emphasize shared responsibilities and equality in the roles of husbands and wives within the family. This research employs inductive, analytical, historical, and critical methods, to compare classical exegetical traditions with contemporary approaches that seek to reinterpret this concept in light of social and cultural changes. The findings indicate that the meaning of qawwamun does not solely refer to male superiority but also encompasses responsibility and leadership based on justice and balance between husband and wife. Therefore, this research recommends re-evaluating the common understanding of a husband's authority in Muslim families.